Optimization of drill geometry and penetration angle for high quality drilling of CFRP/Al hybrid composite - Mohamed Arif, Fatimatuzzahrah (2025)
In recent years, composite materials have become alternative materials in various industries due to their mechanical properties, where they are lightweight and corrosion resistant. Among these, hybrid composites that combine Carbon Fiber Reinforced Plastic (CFRP) and Aluminum (Al) have attracted a lot of attention because of its performance in the aerospace industry. CFRP/Al features with multiple plies of material stacked together in reinforced laminate form, with varying properties throughout the structure, making it ideal for aerospace, automotive, and sports equipment manufacturing. However, the anisotropic nature of these hybrid composites presents unique challenges during the drilling process which often results in hole defects such as delamination, poor surface roughness and burr formation. This research aims to investigate the optimized drill bit design for drilling at various angles to improve hole quality and minimize defects, while increasing the application of CFRP/Al composites. In this study, a matrix planning was employed using the Taguchi method to screen significant factors. From five parameters, including machining parameters, tool geometry features, and drilling angle conditions, three key parameters (point angle, helix angle, and drilling penetration angle) were selected for optimization using Response Surface Methodology (RSM). Through statistical analysis, the remaining parameters were fixed at optimal levels to produce the best hole quality. Two DOEs for entry and exit holes are conducted separately for a comprehensive understanding of the drilling process. In RSM, mathematical regression models and 3D response surface plot have successfully been analyzed to describe the relationships between the key parameters and hole quality. Optimization results indicated that drill geometry with a 124° point angle, 20° helix angle, and a 6° penetration angle is optimal parameter for drilling CFRP/Al. A custom drill bit was developed and validated through experimental work, which showed less than 10% error compared to the predicted values, confirming its accuracy and validity. The customized drill bit design, combined with the optimal penetration angle, demonstrates significant potential for enhancing hole quality and reducing defects in CFRP/Al composites, thereby improving the reliability and cost-efficiency of manufacturing processes within the aerospace industry.